2017
DOI: 10.1002/cpe.4078
|View full text |Cite
|
Sign up to set email alerts
|

A Markovian analytical framework for public‐safety video sharing by device‐to‐device communications

Abstract: Monitoring video of city surveillance camera plays an important role in public security and disaster relief, which is often used by first responder teams, such as firefighters and police officers.The first responders in emergency situations require consistent connection with one another and request the remote real-time monitoring video for effective cooperation and coordination.However, the capacity and privacy of public wireless networks fail to satisfy the requirements in many emergency scenarios, which ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In order to study D2D-based public safety video sharing solutions, Zhao et al studied focal geographic area (FGA) video composed of multiple camera streams. Its bandwidth consumption is higher than that of traditional single-camera streaming, which attracts a large number of content delivery requests in emergency situations [ 7 ]. The article by Zhao et al is mainly based on the application of D2D in public safety video to improve the coverage area of the investigation system and on cloud computing.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study D2D-based public safety video sharing solutions, Zhao et al studied focal geographic area (FGA) video composed of multiple camera streams. Its bandwidth consumption is higher than that of traditional single-camera streaming, which attracts a large number of content delivery requests in emergency situations [ 7 ]. The article by Zhao et al is mainly based on the application of D2D in public safety video to improve the coverage area of the investigation system and on cloud computing.…”
Section: Introductionmentioning
confidence: 99%
“…The DUEs in near proximity can autonomously establish D2D communications even in the nonexistence of a network operator or BS [10]. Hence, safety agencies (e.g., police, hospital, fire station) can rely on D2D communications to deliver information between first responders [11].…”
Section: The Technology Of D2d Communicationsmentioning
confidence: 99%
“…A Monte Carlo simulation was studied, which has shown that the proposed algorithm outperforms the traditional greedy algorithm. In the work of Zhao et al, the authors developed a new traffic burden switching Markovian model to evaluate the performance of transmitting real‐time FGA video in wireless networks with D2D communications. Their results show that the proposed model enables to be a guideline for the deployment and optimization of future wireless video networks with D2D communications.…”
Section: Literature Reviewmentioning
confidence: 99%